+0  
 
0
38
2
avatar+48 

The product of two positive numbers is 53. Express their sum as a function of one of the numbers.

 

I wrote 2 ways:

f(x)=

S=x^2+y^2

x+y=53

y=53-x

x^2+(53-x)^2= S

x^2+2,809-106x+x^2

2x^2-106x+2,809

-b/2a=106/4=26.5

x=26.5

Or

x.y=53

Therefore, y=53/x

x+y=x+53/x

=x^2+53

 

Please tell me where I went wrong (If there's anything I did well in the first place lol) and thank you

 Feb 19, 2019
 #1
avatar+98126 
+3

xy =  53

 

So

 

y =  53/x

 

So....their sum is

 

x + y =

 

x + (53/x)

 

Note that we don't have a particular solution.....for instance   x = 53  and y = 1    works

Or.....x = (53/2)  and y = 2  also works

We can generate infinite answers!!!!

 

 

 

cool cool cool

 Feb 19, 2019
 #2
avatar+48 
+1

You make it so simple. Thank you so much

Roxettna  Feb 19, 2019

14 Online Users

avatar
avatar
avatar